Highly Efficient Mixed Conduction in N‐type Fused Small Molecule Semiconductors. (16th June 2022) - Duan, Jiayao; Zhu, Genming; Wang, Lewen; Chen, Junxin; Cong, Shengyu; Zhu, Xiuyuan; Zhou, Yecheng; Li, Zhengke; McCulloch, Iain; Yue, Wan
Abstract: Highly efficient mixed ionic and electronic conduction is critical to developing high‐performance organic electrochemical transistors (OECTs) devices. While currently, the n‐type small molecules mixed conductors design strategy remains extremely lacking. Herein, ethylene glycol (EG) chain substituted electron‐deficient naphthalene bis‐isatin and rhodanine acceptor units with easily accessible steps are rationally fused, affording fused and planar novel semiconductors with weak intramolecular S–O 'conformation locks', where gNR with EG side chain and hgNR with hybrid alkyl‐EG side chain. The rigid, planar and highly electron‐deficient skeleton enables the resulting small molecule semiconductors to be efficient mixed ionic‐electronic conductors with very high OECT electron mobility up to 0.01 cm 2 V −1 s −1 . Remarkedly, gNR displays the record value of geometry‐normalized transconductance of 0.4 S cm −1 and μC * of 2.6 F V −1 cm −1 s −1, which can also be compared with the state‐of‐art n‐type semiconducting polymers in OECTs. Moreover, the effect of the alkyl spacer on the n‐type mixed ionic and electronic conduction features of the small molecule materials is investigated. The fused electron‐deficient acceptor‐acceptor (A–A) system with intramolecular conformation lock design strategy in this work provides a new avenue to realize next‐generation high‐performance small molecule mixed ionic and electronic conductors for OECT materials. Abstract : Strong electron‐deficient acceptor‐acceptor (A–A) small molecule semiconductors have been designed and synthesized for highly efficient mixed conduction in n‐type organic electrochemical transistors (OECTs). Benefitting from the planar skeleton and intramolecular S–O 'conformation locks', the resulting presentive small molecule semiconductor exhibits high OECT electron mobility up to 0.01 cm 2 V −1 s −1 and μC * of 2.6 F V −1 cm −1 s −1 .